Characterization, inheritance of male sterility and development of male sterile and maintainer lines in ridge gourd (Luffa acutangula (Roxb.) L.) - Varalakshmi B; Rajasekharan P.E. (Journal of Horticultural Sciences, 2022)
Two male sterile mutants IIHRRG-12MS (long fruited) and IIHRRG-28MS (medium long fruited) were identified from the ridge gourd germplasm IIHR-12 and IIHR-28 respectively at ICAR-IIHR, Bengaluru. These two male-sterile (ms) sources were characterized by the production of rudimentary male flowers in the racemes in contrast to the bright yellow flowers with fertile pollen and healthy anthers in male fertile, monoecious plants. Using these ms lines the inheritance of male sterility was worked out, which is cytoplasmic genic male sterility (CGMS) type, with single dominant gene either in homozygous or heterozygous condition restoring male fertility in the presence of sterile cytoplasm. In order to develop F1 hybrids using male sterility, several male sterile and maintainer lines were developed in different genetic back grounds such as green/dark green fruit colour and short/medium long/long fruit length.